Avaliação da incidência e dos fatores de risco da náusea e vômito pós-operatórios em cirurgias buco-maxilo-faciais - Gois, Soraia Rodrigues (2019)
Elective surgeries under general anesthesia are very safe procedures, especially nowadays with the advent of new technologies aimed at giving the patient more and more comfort. However, surgeries still reserve some postoperative complications independent of the area being treated. Among the complications cited, the one that receives less attention from the team, since there is still no well-defined prevention protocol, is postoperative nausea and vomiting (PONV). Nausea is an unpleasant sensation with abdominal discomfort associated with the urge to vomit. Vomiting is the rapid and forced expulsion of gastric contents through the mouth, caused by a strong contraction of the abdominal and diaphragm muscles and supported by the chest and abdominal wall. The persistence of PONV episodes may cause some aggravation to the patient, such as: dehiscence of the surgical wound, dehydration, esophageal rupture, hematoma, hemorrhage, and may in some cases lead to death. Considering the high incidence in surgical procedures of the face and oral cavity, the present study was carried out with the objective of evaluating the incidence of PONV episodes in oral and maxillofacial surgeries under general anesthesia, as well as to identify the main risk factors associated with these episodes. An analytical, observational, retrospective study of documentary analysis of 200 medical records of patients submitted to buco-maxillofacial surgery at the Walter Cantídio University Hospital of the Federal University of Ceará. Sociodemographic data, related to the biotype of each patient, as well as factors related to the type of surgery, access, intubation, blood loss and duration of surgery were collected. The data were analyzed statistically and organized in the form of tables. We found that PONV episodes were recorded in 9% of the sample, with 100% occurring in the first 12 hours postoperatively. Non-smokers undergoing intraoral access surgeries lasting more than 3 hours and greater blood loss showed a higher propensity for PONV episodes. We concluded that the incidence of PONV was 9% in the study population and that the risk factors in the population in question were: non-smokers, aged above 35 years, who underwent orthognathic surgery and who had more than 3 hours of surgery.